2023
DOI: 10.56294/mr202329
|View full text |Cite
|
Sign up to set email alerts
|

The importance of human supervision in the use of ChatGPT as a support tool in scientific writing

Abstract: Introduction: Chat GPT could be a supportive tool in scientific research and writing, allowing researchers to focus on generating results and data analysis. However, it is important to consider possible biases and limitations in text generation, as well as ethical and quality implications in scientific knowledge production. Methods: A literature search was conducted on PubMed and Scopus with the keyword "ChatGPT," establishing inclusion and exclusion criteria to select 10 relevant articles on the use of ChatGP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…Some studies assess the competence of ChatGPT in law school exams (Choi et al, 2023), medical exams (Kung et al, 2023), management (Korzynski et al, 2023), and even in coding assignments (Malinka et al, 2023). Even though some studies found that students' views on ChatGPT were innovative, compatible, and user-friendly (Castillo-González, 2023;Cotton et al, 2023;Raman et al, 2023), some studies found the weaknesses of these systems (Pavlik, 2023). However, after students have their assignments done on ChatGPT, there have been studies discussing the ethical and practical challenges of these platforms (Adiguzel et al, 2023;AlAfnan et al, 2023;Trust et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies assess the competence of ChatGPT in law school exams (Choi et al, 2023), medical exams (Kung et al, 2023), management (Korzynski et al, 2023), and even in coding assignments (Malinka et al, 2023). Even though some studies found that students' views on ChatGPT were innovative, compatible, and user-friendly (Castillo-González, 2023;Cotton et al, 2023;Raman et al, 2023), some studies found the weaknesses of these systems (Pavlik, 2023). However, after students have their assignments done on ChatGPT, there have been studies discussing the ethical and practical challenges of these platforms (Adiguzel et al, 2023;AlAfnan et al, 2023;Trust et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…GPT's ability to generate high-quality text and its adaptability to a wide variety of natural language processing tasks has led to the creation of new applications and opportunities in the field of artificial intelligence. (2,3) The objective of this bibliometric study is primarily focused on describing the knowledge networks (both at the theoretical and country levels) of the Generative Pre-trained Transformer (GPT) as an emerging technology.…”
Section: Introductionmentioning
confidence: 99%
“…19 Optimizing researchers' time in terms of writing scientific articles and improving the quality of these using ChatGPT as an assistant for writing have been proposed. However, this impacts logical thinking and reasoning processes [20][21][22] . Therefore, the need for education in the use of AI is pointed out so that it is beneficial for scientific-technical development in the health area, requiring the will of the states to finance research projects in this research area 8,23 .…”
Section: Introductionmentioning
confidence: 99%